2020
DOI: 10.3389/fpubh.2020.571196
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Knee Pain on Fear of Falling, Changes in Instrumental Activities of Daily Living, and Falls Among Malaysians Age 55 Years and Above

Abstract: Objectives: To determine the temporal relationship between the presence of knee pain and knee pain severity identified at baseline with fall risk, fear of falling and changes in instrumental activity of daily living at 12-months follow-up. Methods: This was a prospective study from the Malaysian Elders Longitudinal Research (MELoR) study involving community dwelling older persons aged 55 years and older. The presence of one fall in the preceding 12 months, knee pain, and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This is due to the fact that this pattern is strongly related to rheumatic and joint diseases, which may increase the risk of older adults developing fear of falling [29,35]. In addition, other studies show that musculoskeletal conditions such as pain and osteoporosis increase the chances of older adults presenting fear of falling by 1.76 (95%CI 1.02; 3.04) [51] and 2.04 (95%CI 1.60; 2.60) [52], respectively. According to the literature, disorders such as pain or chronic conditions would exacerbate the disabling effect of fear of falling, as well as reduce healthy behaviors and patient compliance to treatment [53].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that this pattern is strongly related to rheumatic and joint diseases, which may increase the risk of older adults developing fear of falling [29,35]. In addition, other studies show that musculoskeletal conditions such as pain and osteoporosis increase the chances of older adults presenting fear of falling by 1.76 (95%CI 1.02; 3.04) [51] and 2.04 (95%CI 1.60; 2.60) [52], respectively. According to the literature, disorders such as pain or chronic conditions would exacerbate the disabling effect of fear of falling, as well as reduce healthy behaviors and patient compliance to treatment [53].…”
Section: Discussionmentioning
confidence: 99%
“…This condition limits activities and can cause significant muscle atrophy, loss of balance, gait disorder, functional activity limitations, and changes in physical condition, all of which may lead to an increased risk of falls. [3,10] Our findings showed that patients with knee OA and a history of falls had higher KOOS symptom scores than those without previous falls. These results are consistent with those reported by a previous study [33] in which authors observed a higher KOOS symptom score in patients with knee OA, which indicates loss of functional capacity, which leads to reduced lower extremity muscle strength and a high risk of falls.…”
Section: Discussionmentioning
confidence: 62%
“…This condition limits activities and can cause significant muscle atrophy, loss of balance, gait disorder, functional activity limitations, and changes in physical condition, all of which may lead to an increased risk of falls. [3,10]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, male adults have been considered to be stronger in the lower limbs than their female counterparts ( Ditroilo et al, 2010 ), and in the KOA cohort, female patients have been reported to have more severe impairments in lower extremity neuromuscular control than male patients. However, a recent large-sample, prospective investigation based in an Asian community suggested that muscle strength was not associated with fear of falling ( Mat et al, 2020 ), signifying the need of further investigations regarding the characteristics of neuromuscular control during walking, as this remains the most common functional activity where fall accidents occur ( Promsri et al, 2023 ). To date, a gender difference on lower limb proprioception has been investigated in healthy cohorts, and some clinical populations ( Karkousha, 2016 ; Lu et al, 2022 ; Shi et al, 2023a ), yet not in KOA ( Salamanna et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%